Pro‐osteoclastic in vitro effect of Polyethylene‐like nanoparticles: Involvement in the pathogenesis of implant aseptic loosening. Issue 11 (14th June 2016) - Brulefert, Kevin; Córdova, Luis A.; Brulin, Bénédicte; Faucon, Adrien; Hulin, Philipe; Nedellec, Steven; Gouin, François; Passuti, Norbert; Ishow, Eléna; Heymann, Dominique
Abstract: Polyethylene micro‐sized wear particles released from orthopedic implants promote inflammation and osteolysis; however, less is known about the bioactivity of polyethylene nanosized wear particles released from the last generation of polymer‐bearing surfaces. We aim to assess the internalization of fluorescent polyethylene‐like nanoparticles by both human macrophages and osteoclasts and also, to determine their effects in osteoclastogenesis in vitro . Human macrophages and osteoclasts were incubated with several ratios of fluorescent polyethylene‐like nanoparticles between 1 and 72 h, and 4 h, 2, 4, 6, and 9 days, respectively. The internalization of nanoparticles was quantified by flow cytometry and followed by both confocal and video time‐lapse microscopy. Osteoclast differentiation and activity was semiquantified by tartrate‐resistant acid phosphatase (TRAP) staining, TRAP mRNA relative expression, and pit resorption assay, respectively. Macrophages, osteoclast precursors and mature osteoclasts internalized nanoparticles in a dose‐ and time‐dependent manner and maintained their resorptive activity. In addition, nanoparticles significantly increased the osteoclastogenesis as shown by upregulation of the TRAP expressing cell number. We conclude that polyethylene‐like nanosized wear particles promote osteoclast differentiation without alteration of bone resorptive activity of mature osteoclasts and they could be considered as important actors in periprosthetic osteolysis of the last new generation of polymer‐bearing surfaces. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2649–2657, 2016.